Management of Aberrant Frenal Attachments in Adults by Scalpel Method and 980 nm Diode Laser - Jaahnavi Lanka; Pratibha Gopalkrishna; Santhosh Kumar (Case Reports in Dentistry)
Treatment modalities like electrosurgery and lasers have emerged as effective painless alternatives to scalpel methods for a frenectomy. The present case series involves ten patients, diagnosed with abnormal frenal attachments. Frenectomy was performed by 980 nm diode laser and scalpel methods. Scalpel frenectomy was performed as described by Archer and Kruger. Laser-assisted frenectomy was performed by a hemostat-guided incision using a 980 nm diode laser tip in a paintbrush motion. It was observed that Visual Analogue Scale (VAS) pain scores in patients who underwent scalpel frenectomy were comparatively higher than the laser-treated patients. In contrast, wound healing scores were higher in the scalpel group, suggesting early wound healing in the scalpel-treated patients.